2012
DOI: 10.1002/jtr.1877
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model for Examining how Destination Image, Perceived Value, and Service Quality Affect Destination Loyalty: a Case Study of Orlando

Abstract: The primary objectives of this study were to investigate and develop a theoretical relationship among destination image, service quality and perceived value and to empirically test the constructs that are likely to affect tourist satisfaction, which in turn influence revisit intentions and word‐of‐mouth referrals. The results of empirical study indicated that destination image influences service quality and perceived value. In addition, the findings revealed that perceived value has a significant effect on sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
166
0
15

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(206 citation statements)
references
References 80 publications
25
166
0
15
Order By: Relevance
“…A majority of studies that emphasize the important of tourists' motivation based on the concept of push motivation (psychological needs) and pull motivation (attraction of the destination) in choosing vacation destination choices have been generally accepted (Kim, Holland & Han 2013).…”
Section: This View Originates From the Motivation Theories (Lopes 201mentioning
confidence: 99%
“…A majority of studies that emphasize the important of tourists' motivation based on the concept of push motivation (psychological needs) and pull motivation (attraction of the destination) in choosing vacation destination choices have been generally accepted (Kim, Holland & Han 2013).…”
Section: This View Originates From the Motivation Theories (Lopes 201mentioning
confidence: 99%
“…The data was gathered through highly structured questionnaire designed based on scales and items adapted from previous research. Core service quality was measured based on Danaher and Mattsson (1994) research, overall value used Kim et al (2013), customer engagement was based on Vivek et al (2014) and future behavioural intentions borrowed item from Garbarino and Johnson (1999). Item measuring behavioural intentions is "In future I plan to attend shows at HNK".…”
Section: Methodsmentioning
confidence: 99%
“…The research also examines the direction and strength of the influence of overall value and core service quality on the customer engagement. The data was gathered through highly structured questionnaire designed based on scales and items adapted from previous research i. e. Vivek et al (2014), Danaher and Mattsson (1994), Kim et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have shown that perceived value influences loyalty both directly and indirectly [18]. The relationship among perceived value, satisfaction, and loyalty has been examined by researchers who focused on the relating paths between perceived value and satisfaction [6], and between perceived value and loyalty [19].…”
Section: Perceived Valuementioning
confidence: 99%